2006
DOI: 10.1590/s0101-31222006000300010
|View full text |Cite
|
Sign up to set email alerts
|

Teste de envelhecimento acelerado em sementes de pimenta

Abstract: , DANIEL DOS SANTOS PORTOCARRERO NAVEIRA 4 RESUMO -O presente trabalho teve por objetivo adequar a metodologia do teste de envelhecimento acelerado para a avaliação do vigor de sementes de pimenta. Sementes de seis lotes foram submetidas aos testes de germinação, primeira contagem de germinação, germinação a baixa temperatura e envelhecimento acelerado. Para o teste de envelhecimento acelerado, foram testados os métodos tradicional (100% UR) e modificado (76% UR), nas temperaturas de 38, 42 e 45ºC durante os p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
14

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 13 publications
(12 reference statements)
2
8
0
14
Order By: Relevance
“…In the freezer environment, seeds kept in multiwall-paper packaging or in PETE bottles (Figure 4). Small seeds absorb water more quickly and less uniformly during the ageing period, which may accelerate the deterioration process or result in variations in behaviour between seeds of a single sample interfering with the accuracy of the results (BHERING et al 2006). Abreu et al (2011) observed that the stress condition imposed by the accelerated ageing test greatly reduced the number of normal sunflower seedlings after nine months of storage.…”
Section: Resultsmentioning
confidence: 99%
“…In the freezer environment, seeds kept in multiwall-paper packaging or in PETE bottles (Figure 4). Small seeds absorb water more quickly and less uniformly during the ageing period, which may accelerate the deterioration process or result in variations in behaviour between seeds of a single sample interfering with the accuracy of the results (BHERING et al 2006). Abreu et al (2011) observed that the stress condition imposed by the accelerated ageing test greatly reduced the number of normal sunflower seedlings after nine months of storage.…”
Section: Resultsmentioning
confidence: 99%
“…Os resultados foram expressos em μS cm -1 g -1 de sementes (Vidigal et al, 2008). Envelhecimento acelerado: Uma única camada de sementes foi colocada sobre tela metálica acoplada à caixa plástica gerbox, contendo 40 mL de água deionizada, e colocadas em câmara de germinação pelo período de 96 horas a 42 °C (Bhering et al, 2006). Após, o processo de envelhecimento as sementes foram semeadas em gerbox, a contagem foi realizada aos sete dias (Primeira contagem de germinação) após a instalação do teste, de acordo com os critérios estabelecidos pelas Regras de Análise de Sementes (Brasil, 2009).…”
Section: Methodsunclassified
“…It is important to stress that the vigor tests have specific evaluation principles. The physiological potential of the seeds is a reflection of a set of characteristics determined by the germination and vigor tests, which identify their capacity to present adequate performance when the seeds are exposed to different environmental conditions (Bhering, Dias, Vigial, & Naveira, 2006). Note.…”
Section: Resultsmentioning
confidence: 99%
“…The physiological potential of the seeds is a reflection of a set of characteristics determined by the germination and vigor tests, which identify their capacity to present adequate performance when the seeds are exposed to different environmental conditions (Bhering, Dias, Vigial, & Naveira, 2006). Therefore, the use of this information allows, in a safe way, to verify the behavior of the seeds, which directly influences the decision making for selection of lots with high and low vigor.…”
Section: Introductionmentioning
confidence: 99%